2015
DOI: 10.3109/07357907.2015.1064534
|View full text |Cite
|
Sign up to set email alerts
|

RG7112, a Small-Molecule Inhibitor of MDM2, Enhances Trabectedin Response in Soft Tissue Sarcomas

Abstract: MDM2 is a critical negative regulator of the p53 tumor suppressor protein. Selected sarcoma subtypes are being treated with Trabectedin in second line, which promotes DNA damage and p53-dependent apoptosis. The aim of this study was to evaluate the improvement of Trabectedin response with MDM2 inhibitors in soft tissue sarcomas. The antitumor effects of Trabectedin, Nutlin-3A and RG7112 as single agents or in combination were examined in vitro. RG7112 significantly synergized with Trabectedin in MDM2-amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Besides, the synergistic effect was observed in LNCaP when combined with androgen ablation, leading to a significant tumor regression 24 . Recently, Obrador-Hevia and co-workers 35 found that RG7112 can significantly enhance the response of Trabectedin to MDM2-amplified liposarcoma cells. Clinical pharmacological studies showed that high/low-fat food and new formulation can enhance bioavailability; high-dose consecutive daily dosing for 3–5 days can yield required high drug exposures and PD effects for cancer therapy 36 .…”
Section: Development Of Mdm2/x Inhibitors For Cancer Therapymentioning
confidence: 99%
“…Besides, the synergistic effect was observed in LNCaP when combined with androgen ablation, leading to a significant tumor regression 24 . Recently, Obrador-Hevia and co-workers 35 found that RG7112 can significantly enhance the response of Trabectedin to MDM2-amplified liposarcoma cells. Clinical pharmacological studies showed that high/low-fat food and new formulation can enhance bioavailability; high-dose consecutive daily dosing for 3–5 days can yield required high drug exposures and PD effects for cancer therapy 36 .…”
Section: Development Of Mdm2/x Inhibitors For Cancer Therapymentioning
confidence: 99%
“…When this is combined with MDM2 inhibitors, both stability and activity of p53 are increased, leading to pronounced cell death. The DNA damaging drug Trabectedin, currently used in second line for treating soft tissue sarcoma, was also reported to synergize with the MDM2 inhibitor RG7112 46 , perhaps as a result of p53 accumulation (through MDM2 inhibition) and activating p53 modifications (through DNA damage response). In preclinical investigations and cell culture, MDM2 antagonists also cooperated efficiently with mitogen-activated protein kinase kinase (MEK) or phosphatidylinositol-3 kinase (PI3K) inhibitors, BH3 mimetics, BCR-ABL antagonists, and histone deacetylase inhibitors 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation and apoptosis assays. Real-time cell proliferation and viability after treatment with doxorubicin or nilotinib, as single agents or in sequential combination, was performed on SW982 cells, using the xCELLigence System as described previously (24). Analysis of the cell cycle by flow cytometry was performed on SW872 cells as described previously (16).…”
Section: Methodsmentioning
confidence: 99%